"In the execution of his office": lay officials and the exercise of ecclesiastical discipline in Scotland, c. 1600-1660. Issue 5 (20th October 2018) - Langley, Chris R.
ABSTRACT: Consistorial discipline was central to the application of Reformed Christianity in early-modern Scotland. This article argues that both elders and deacons were frequently drawn into personal disputes that were more communal than theological. Neighbours' complaints served to emphasise Reformed ideals of honesty and good reputation but could also undermine the foundations of Reformed discipline. In response, consistories across Scotland came to identify disputes involving one official as slights on the entire session. While officials were reliant on an increasing sense of corporate identity to protect them, neighbours' involvement shows the degree of lay support and participation in the Reformed Church.